2008
DOI: 10.1248/cpb.56.715
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 6-(Methylsulfinyl)hexyl Isothiocyanate (6-MITC) and Its Conjugate with N-Acetyl-L-cysteine (NAC) by High Performance Liquid Chromatograpy-Atmospheric Pressure Chemical Ionization Mass Spectrometry (HPLC-MS/APCI)

Abstract: Previous reports have documented that some isothiocyanates (ITCs) prevent the formation of cancers in animal models.1-4) 6-(Methylsulfinyl)hexyl isothiocyanate (6-MITC) is found in wasabi (Wasabia japonica), a Japanese indigenous herb, and a variety of studies on the anticancer properties of 6-MITC have been described, 5,6) with 6-MITC attracting great attention as a new possible candidate for controlling cancer cell progression and metastasis. Anticancer activity of 6-MITC in vitro was studied with a human ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…A third compound whose retention time is close to that of proITC, was however found to be structurally different. Similar findings were mentioned in previous studies [19, 21]. Using LC–UV, Liang et al [19] identified SFN in 18 varieties of Chinese cabbage, and estimated its contents in the range of 0.7–5.3 μg g −1 of fresh weight.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…A third compound whose retention time is close to that of proITC, was however found to be structurally different. Similar findings were mentioned in previous studies [19, 21]. Using LC–UV, Liang et al [19] identified SFN in 18 varieties of Chinese cabbage, and estimated its contents in the range of 0.7–5.3 μg g −1 of fresh weight.…”
Section: Resultssupporting
confidence: 84%
“…In order to confirm peak identities and molecular mass, ITC-mce was analyzed by LC–MS, a method widely used for neutral compounds [21]. In the negative mode, the derivatives of MITC, SFN (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lewis et al (2015) reported that AITC inactivates protein tyrosine phosphatase via modification of the active site Cys-215. 6-MSITC was reported to conjugate with a thiol group of N-acetyl-L-cysteine (Yamaguchi et al, 2008) and a cysteine residue of heat shock protein 90β (Shibata et al, 2011). In this study, 6-MSITC stimulated human DPCs.…”
Section: Resultsmentioning
confidence: 64%
“…That is, the methylthioalkyl isothiocyanate but not the methylthioalkylamine has the induction potency of glutathione S-transferase (GST) activity, indicating that the isothiocyanate moiety is essential for the induction of GST activity. 6-MITC and N-acetyl cysteine have been reported to spontaneously make conjugates in aqueous solution [14]. Compounds 2b, 2c, 2d and 2f had almost identical antiproliferative and anti-NO production activities as those of 6-MITC.…”
Section: Inhibitory Activities Against In-vitro Growth Of Tumor Cellsmentioning
confidence: 94%